Educational institutions as a path to reducing drug abuse among youth: the Icelandic experience (Entrepreneurship Journal for Finance and Business, 2024)
Due to the seriousness of drug abuse, especially among young people, the researchers emphasize the importance of educational institutions in curbing this phenomenon. Schools serve as a bridge between youth, their families, and society, playing a crucial role in educating young people about the dangers of drug use and addiction, and guiding them toward healthy alternative activities. This research highlights the Icelandic experience as a successful model from the 1990s, where innovative programs and awareness efforts were implemented in collaboration with local entities to reduce drug abuse.